Natural Equivalence in Literal Translation: A Case Study of the Bilingual Magazine LINGO - I Gusti Agung Gede Alit Dwi Arcana; Hikmaharyanti, Putu Desi Anggerina (Kajian Linguistik dan Sastra, 2024)
Literal translation is often used to maintain fidelity to the source text when translating into the target language. This study focuses on the application of the concept of natural equivalence in the context of literal translation in the bilingual magazine LINGO. The main objective of this study is to explore the extent to which literal translation is used in LINGO and how natural equivalence can be achieved to improve the quality of translation. The research method involves an in-depth analysis of the original and translated texts of LINGO magazine to assess the use of literal equivalents and their impact on the naturalness of the target language. The study also aims to identify areas where natural equivalence could be better used, and to suggest strategies for overcoming the problems associated with overly literal translation. The implication of these findings is the importance of using natural equivalence in translation to improve the readability and naturalness of the text. Since 53% of translation methods employed are based on literal translation, it is expected that this study provides valuable insights into the application of the concept of natural equivalence in literal translation, and a basis for further research to improve translation practices in bilingual publications.